Tau Abnormalities and Autophagic Defects in Neurodegenerative Disorders; A Feed-forward Cycle: - Samimi, Nastaran; Asada, Akiko; Ando, Kanae (Galen Medical Journal, 2020)
Abnormal deposition of misfolded proteins is a neuropathological characteristic shared by many neurodegenerative disorders including Alzheimer’s disease (AD). Generation of excessive amounts of aggregated proteins and impairment of degradation systems for misfolded proteins such as autophagy can lead to accumulation of proteins in diseased neurons. Molecules that contribute to both these effects are emerging as critical players in disease pathogenesis. Furthermore, impairment of autophagy under disease conditions can be both a cause and a consequence of abnormal protein accumulation. Specifically, disease-causing proteins can impair autophagy, which further enhances the accumulation of abnormal proteins. In this short review, we focus on the relationship between the microtubule-associated protein tau and autophagy to highlight a feed-forward mechanism in disease pathogenesis. [GMJ.2020;9:e1681]